2021
DOI: 10.3762/bjoc.17.148
|View full text |Cite
|
Sign up to set email alerts
|

Post-functionalization of drug-loaded nanoparticles prepared by polymerization-induced self-assembly (PISA) with mitochondria targeting ligands

Abstract: Herein, the postfunctionalization of different non-fouling PISA particles, prepared from either poly(oligo ethylene glycol methyl ether methacrylate) (pPEGMA) and the anticancer drug PENAO (4-(N-(S-penicillaminylacetyl)amino)phenylarsenonous acid) or zwitterionic 2-methacryloyloxyethyl phosphorylcholine (MPC) and PENAO were reported. Both PISA particles were reacted with triphenylphosphonium (TPP) as mitochondria targeting units in order to evaluate the changes in cellular uptake or the toxicity of the conjuga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…39 In more recent reports by Stenzel et al , the anticancer drug 4-( N -( S -penicillaminylacetyl)amino)phenylarsenonous acid (PENAO) methacrylate prodrug was copolymerized with OEGMA or zwitterionic 2-methacryloyloxyethyl phosphorylcholine (MPC) to synthesize macro-CTAs for PISA. 42,43 The prepared nanoparticles with drug covalently linked to shell block were compared in terms of cytotoxicities, cellular uptakes, spheroid penetration, and cell localization profiles.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…39 In more recent reports by Stenzel et al , the anticancer drug 4-( N -( S -penicillaminylacetyl)amino)phenylarsenonous acid (PENAO) methacrylate prodrug was copolymerized with OEGMA or zwitterionic 2-methacryloyloxyethyl phosphorylcholine (MPC) to synthesize macro-CTAs for PISA. 42,43 The prepared nanoparticles with drug covalently linked to shell block were compared in terms of cytotoxicities, cellular uptakes, spheroid penetration, and cell localization profiles.…”
Section: Applicationsmentioning
confidence: 99%
“…20 Up to now, many morphologies have been realized via PISA, including spheres, rods, worms, vesicles, framboidal vesicles, 21,22 multilamellar vesicles, 23 lamellae, 24 spongosomes, [25][26][27][28][29][30][31] hexosomes, [25][26][27]32 cubosomes, 25,26,32 Janus particles, 33,34 colloidal molecules, 33,34 and many others. The synthesized particles have a broad range of applications in the areas of biomedical, [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] coating, 54,55 catalysis [56][57][58][59][60] and Pickering emulsions 22,[61]<...…”
Section: Introductionmentioning
confidence: 99%
“… It resulted in polymer prodrug micelles of 30–40 nm in diameter that exhibited tunable cytotoxicity as a function of the PMPC chain length: reducing the PMPC chain length from 37 to 13 repeating units led to a 5-fold increase in cytotoxicity. These nanoparticles can be postfunctionalized on their surface by triphenylphosphonium (TPP) as a mitochondria targeting agent, resulting in an improvement of tumor penetration and cytotoxicity . Interestingly, when OEGMA was used instead of MPC, the surface functionalization of resulting nanoparticles by TPP had little effect on their biological performances, likely because of a higher steric hindrance around TPP moieties caused by OEGMA side chains compared to MPC moieties.…”
Section: Polymerization-induced Self-assembly (Pisa)mentioning
confidence: 99%
“…These nanoparticles can be postfunctionalized on their surface by triphenylphosphonium (TPP) as a mitochondria targeting agent, resulting in an improvement of tumor penetration and cytotoxicity. 120 Interestingly, when OEGMA was used instead of MPC, the surface functionalization of resulting nanoparticles by TPP had little effect on their biological performances, likely because of a higher steric hindrance around TPP moieties caused by OEGMA side chains compared to MPC moieties.…”
Section: Poly[2-(methacryloyloxy) Ethyl Phosphorylcholine] (Pmpc)mentioning
confidence: 99%
“…On the other hand, the mitochondrial membrane potential generally ranges between −150 and −180 mV in vivo, which is much higher than that of other cellular organelles. , These two characteristics enable TPP to be easily accumulated in mitochondria and thus be widely used in mitochondria-targeted drug design, and the conjugation of the lipophilicphosphonium cation to pharmaceutic molecules may change its physical properties and affect its penetration through cell membranes. Cationic amphiphilic compounds have biological activities such as antibacterial, antifungal, antiprotozoal, antitumor, and immunomodulatory effects. In our previous studies, we have shown the potential of this strategy in the novel fungicide development targeting respiratory chain complexes. , …”
Section: Introductionmentioning
confidence: 99%